2008
DOI: 10.2478/s11686-008-0008-9
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Echinococcus multilocularis (Cestoda, Taeniidae) in red foxes (Vulpes vulpes) from Western Ukraine

Abstract: Echinococcus multilocularis was found for the first time in red foxes in the L'vivska and Volynska regions (Western Ukraine). Prevalence was 36% and intensity was 11-731 parasites. The material was identified as E. multilocularis on morphological characters. It is presumed that this infection of foxes with E. multilocularis occurred locally and, probably, can be considered as a consequence of the expansion of the range of the parasite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
1
9
0
2
Order By: Relevance
“…In southern areas bordering with northern Slovakia the prevalence exceeds 40.0 % (Borecka et al, 2008). Karamon et al (2010) in recent survey found a significant increase in prevalence in eastern Poland in Lubelskie province (from 1.0 % to 18.2 %). Since 1992, 76 human alveolar echinococcosis cases were diagnosed in Poland.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In southern areas bordering with northern Slovakia the prevalence exceeds 40.0 % (Borecka et al, 2008). Karamon et al (2010) in recent survey found a significant increase in prevalence in eastern Poland in Lubelskie province (from 1.0 % to 18.2 %). Since 1992, 76 human alveolar echinococcosis cases were diagnosed in Poland.…”
Section: Discussionmentioning
confidence: 93%
“…In 2008 was reported the first finding of E. multilocularis also in western region of Ukraine bordering the eastern Slovakia. Considering that no human cases are registered from this area to date, a new focus of infection is supposed to arise only recently (Kharchenko et al, 2008). An extensive research of alveolar echinococcosis was in progress in 2008 and 2009 in Hungary.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to the prevalence of infection in foxes in Belgium (24.55%) [33], Switzerland (47%–67%) [26], Ukraine (36%) [34], Kyrgyzstan (64%) [35], and Japan (49%) [36], it is assumed that Razavi Khorasan Province is hyperendemic for this tapeworm.…”
Section: Discussionmentioning
confidence: 99%
“…Ukraine (Kharchenko et al, 2008), Slovakia (Miterpáková et al, 2006), Poland (Malczewski et al, 2008), the Netherlands (Giessen et al, 1999;Borgsteede et al, 2003 ), Germany (Friedland et al, 1985), France (Houin et al, 1982), Switzerland (Hofer et al, 2000;Stieger et al, 2002), Belarus (Merkusheva & Bobkova, 1981;Shimalov & Shimalov, 2003), Russia (Key..., 1978), Estonia (Moks et al, 2005). Whether the range of E. multilocularis, as recognized today, is the result of an expansion or more intensive investigations is not known because of the lack of historical data.…”
Section: Discussionmentioning
confidence: 98%